2017
DOI: 10.1097/md.0000000000009210
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum TGF-β1 level in atrial fibrosis and outcome after catheter ablation for paroxysmal atrial fibrillation

Abstract: This study aimed to evaluate the relationship between serum transforming growth factor-β1 (TGF-β1) concentration and atrial fibrosis and to determine whether plasma TGF-β1 concentration is an independent predictor of atrial fibrillation (AF) recurrence after catheter ablation.We included 98 consecutive patients who underwent catheter ablation, including 38 with paroxysmal AF (AF group) and 60 with paroxysmal supraventricular tachycardia (control group). We compared their preablation serum concentration of biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
15
0
2
Order By: Relevance
“…Serum TGF-beta1, which was previously discussed as part of the fibrotic pathway, has a strong positive correlation with areas of low endocardial atrial voltage consistent with fibrosis (r[ 2 ]=0.93; p<0.001). [ 93 ] In addition, TGFbeta1 expression is specifically upregulated in patients with extensive low-voltage areas undergoing ablation. [ 94 ] Serum TGF-beta1 has been shown to be an independent risk factor for AF recurrence after ablation in both paroxysmal and persistent AF.…”
Section: Clinical Evaluation Of Myopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Serum TGF-beta1, which was previously discussed as part of the fibrotic pathway, has a strong positive correlation with areas of low endocardial atrial voltage consistent with fibrosis (r[ 2 ]=0.93; p<0.001). [ 93 ] In addition, TGFbeta1 expression is specifically upregulated in patients with extensive low-voltage areas undergoing ablation. [ 94 ] Serum TGF-beta1 has been shown to be an independent risk factor for AF recurrence after ablation in both paroxysmal and persistent AF.…”
Section: Clinical Evaluation Of Myopathymentioning
confidence: 99%
“…[ 94 ] Serum TGF-beta1 has been shown to be an independent risk factor for AF recurrence after ablation in both paroxysmal and persistent AF. [ 93 , 95 ] Interestingly, Kishima et al found lower concentrations of TGF-beta1 in patients with recurrence after ablation. [ 96 ] They suggested that the discrepancy may be related to the inflammatory state of the patient.…”
Section: Clinical Evaluation Of Myopathymentioning
confidence: 99%
“…Several prospective studies in human subjects have implicated TGF-β1 as an independent predictor of RAF following ablation therapy. [70][71][72][73][74][75] Additionally, a study by Cao et al 76 demonstrated that polymorphisms in TGF-β1 gene promotors may be useful in predicting the prognosis of patients in Chinese populations following ablative therapy for AF. Similar to TGF-β1, matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) have been associated with AF, due to their role in ECM metabolism.…”
Section: Fibrotic Remodeling In Rafmentioning
confidence: 99%
“…However, no significant correlation was reported in 154 patients with paroxysmal AF. 74 Tian et al 70 found that serum TGF-β1 concentrations prior to catheter ablation were predictive of RAF in a group of 38 patients with paroxysmal AF. 70 The findings of these two studies indicate a potential role of TGF-β1 to predict RAF.…”
Section: Tgf-β1mentioning
confidence: 99%
“…For instance, atrial fibrotic remodeling was reported to be associated with the development and persistence of atrial fibrillation (AF). 16,17) And adipose tissue fibrosis was reported to be a major contributor to insulin resistance in obesity. 18) However, the association between circulating TSP2 levels and the prevalence of AF or insulin resistance remains to be investigated in the general population.…”
mentioning
confidence: 99%